Los institutos armados y el tema de los Derechos Humanos - Cedeño Castro, Rogelio (2008)
The discusión on the Tepic of Human rigsts has resulted in endless debate, a kina of the Topic and tose who pose the need to recognize the economic ahd social rights as something more than an expectation. The theme of rights, hypocritically handley by various social and political actors, has been reduced recognition of civil liberties, which are inoperative by large majorities in Latin America not only excluded from access to wealth, but also education and culture.